How Did the Housing and Labor Market Crises Affect Young Adults' Living Arrangements? - William H. Rogers; Anne E. Winkler (Institute for the Study of Labor (IZA), 2014)
The housing and labor market crises of the late 2000s left few families and individuals unscathed. In the wake of these events, evidence points to more "doubling-up" of families in the same household. To what extent have these crises affected individuals' decisions to live independently? What differentiates this study from others is the careful attention paid to the role of housing market conditions as measured by MSA-level housing prices, rents, and foreclosure rates on this decision. The empirical analysis is conducted by appending data on area-level conditions for 85 of the largest MSAs in the United States to individual-level data from the ACS PUMS on living arrangements of young adults ages 22 to 34 living in these MSAs. The analysis spans the period 2005 (pre-crisis) through 2011. Within this time period, all MSAs experienced a rise in housing prices, a peak, and then a decline. Regarding the area-level variables, we find a robust statistically significant effect for rent only. Our broader conclusion is that it is individual-level factors, not area-level conditions that largely lie behind young adults' living arrangement decisions.
Keywords: J12; R23; 330; living arrangements; labor market; housing market; foreclosures